IMPLEMENTING DIGITAL OVERSIGHT OF THE SUPPLY CHAIN ECOSYSTEM THROUGH LOGISTICS CONTROLLING - LESNIKOV, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The increasing dynamism of economic environments, the proliferation of competitive-cooperative ties among producers, and growing market volatility have undermined the effectiveness of linear interactions among supply chain participants. Despite the widespread implementation of information systems, many supply chain actors experience delays in data exchange and accessing predictive analytics. These challenges are primarily attributed to the underdevelopment of logistics flow processes and the lack of transparency and clarity in business logic, impeding strategic and operational decision-making. This study aims to advance the theoretical and practical foundations for organizing logistics controlling in the strategic management of supply chain ecosystems, drawing on the achievements of the Fourth Industrial Revolution and leveraging modern tools for managing logistics activities. The research methodology is grounded in organizational ecology, logistics controlling principles, formal logic, and first- and second-order predicates to model business processes within the supply chain ecosystem. The article proposes a conceptual framework for digital supply chain surveillance as an extension of traditional logistics control, shifting the focus towards big data and predictive analytics. A structured supply chain ecosystem business object model is developed, comprising physical entities, role-based actors, and institutional-structural components. An object-oriented modeling approach is presented, employing a Value Added Diagram (VAD) to visualize value stream formation. Predicate expressions are introduced to formalize the states of business objects and their transitions, enabling the construction of models at any level of detail and the specification of attributes critical for digital oversight. The practical significance of this work lies in providing a methodological foundation for implementing digital surveillance systems that ensure the continuity of information flow among participants in the logistics ecosystem, enhance its adaptability, and support the timely adjustment of logistics operations.